Análise de produções contemporâneas do Serviço Social que versam a interseccionalidade de raça e gênero, sobre corpos de mulheres negras - Silva, Kannanda Emilly Padilha da (Universidade Federal do Tocantins, 2023)
In this research, we aimed to analyze the delimited contents that were based on the transversality of gender and race, and that cross the dimension of the bodies of sexualized and racialized women (des) in the area of Social Work, and the implications for the professional exercise. The importance of the discussion about the racial issue and the sexualization of black female bodies, thinking about the social spaces occupied by them and the social relations of oppression, is necessary to understand the racist and sexist patterns and stereotypes that the dominant ideology instituted to black bodies, discourses that were naturalized over time in the Brazilian social formation. Dealing with racism and sexism, as structuring capitalism in Brazil, is necessary to understand the social relations from which they establish expressions of the Social Question, and which are inherent in the support of this system. Bourgeois hegemony uses control technologies to reinforce the socially accepted and imposed standard. Considering the relations of domination-exploration in its entirety, we start from the qualitative methodology, articulated to content analysis, documentary and bibliographic research was worked in feminist perspectives.